An Examination of Attachment In Afterschool Programs - Jackson, Ariana V. (East Carolina University)
While children and adolescents typically spend from six to seven hours a day in formal school settings, they are often faced with a glut of free time. Estimates put between 40-50% of a child’s waking hours spent in what is described as discretionary time. Advocates of afterschool programs (ASPs) identify the non-school hours as an important time to make an impact on youth vulnerable to risks related to delinquency and school failure. ASPs are places where young people can develop attachments to positive adult role models and prosocial peers. These programs are designed to reinforce educational goals, while promoting opportunities for positive development through structured recreation and enrichment opportunities. Considering the salience of attachment for healthy development of youth, it is important to understand how the features of youth programs associate with the bonds between youth and prosocial adults who oversee these programs. Several studies have identified specific supports for competence and autonomy, and these align well with attachment’s roots in the presence of a supportive environment. The purpose of this study was to examine the relationships between the provision of staff supports for autonomy and competence with the attachment that youth report toward ASPs, and how staff supports and attachment to ASPs associate with school attachment. The study acquired data from three 21st Century Community Learning Centers in eastern North Carolina. Data were collected from 171 youth program participants in grades 2-12 using electronic questionnaires. Supports for autonomy and competence were measured using adaptations of scales developed to study self-determination theory. School attachment was measured through a scale developed by Resnick et al. (1997). Logistic regression tests were used to test study hypotheses. Results supported both hypotheses as supports for competence and autonomy were associated with afterschool attachment, and afterschool attachment was positively related to overall school attachment. Autonomy and competence work to support long-term engagement in programs by appealing to affective components to enhance relatedness.
Keywords: Recreation; Autonomy; Competence; Connectedness; Attachment behavior in children.; After-school programs--North Carolina.; Community centers--North Carolina.